2004
DOI: 10.1007/s00787-004-0353-7
|View full text |Cite
|
Sign up to set email alerts
|

Not EEG abnormalities but epilepsy is associated with autistic regression and mental functioning in childhood autism

Abstract: The aim of the study was to investigate the potential association of epilepsy and EEG abnormalities with autistic regression and mental retardation. We examined a group of 77 autistic children (61 boys, 16 girls) with an average age of 9.1 +/- 5.3 years. Clinical interview, neurological examination focused on the evaluation of epilepsy, IQ testing, and 21-channel EEG (including night sleep EEG recording) were performed. Normal EEGs were observed in 44.4% of the patients, non-epileptiform abnormal EEGs in 17.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
3
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 21 publications
6
79
3
5
Order By: Relevance
“…98 Epileptiform abnormalities on electroencephalography (EEG) are common in children with ASDs, with reported frequencies ranging from 10% to 72%. 99 Some studies have suggested that epileptiform abnormalities on EEG 100 and/or epilepsy 101 are more common in the subgroup of children with ASDs who have a history of regression, whereas other studies have not demonstrated this association. 102,103 Autistic regression with epileptiform abnormalities on EEG has been compared by analogy with Landau-Kleffner syndrome and electrical status epilepticus in sleep, but there are important differences between these conditions, and the treatment implications are unclear.…”
Section: Seizuresmentioning
confidence: 99%
“…98 Epileptiform abnormalities on electroencephalography (EEG) are common in children with ASDs, with reported frequencies ranging from 10% to 72%. 99 Some studies have suggested that epileptiform abnormalities on EEG 100 and/or epilepsy 101 are more common in the subgroup of children with ASDs who have a history of regression, whereas other studies have not demonstrated this association. 102,103 Autistic regression with epileptiform abnormalities on EEG has been compared by analogy with Landau-Kleffner syndrome and electrical status epilepticus in sleep, but there are important differences between these conditions, and the treatment implications are unclear.…”
Section: Seizuresmentioning
confidence: 99%
“…In addition to an increased prevalence of epilepsy in individuals with ASD, there is also a marked increased incidence of epileptiform activity on the EEGs of people with ASD (Giovanardi et al 2000;Hrdlicka et al 2004;Canitano et al 2005;Gabis et al 2005;Hughes and Melyn 2005;Baird et al 2006;Chez et al 2006;Kim et al 2006;Akshoomoff et al 2007;Hara 2007;Parmeggiani et al 2007;Giannotti et al 2008;Spence and Schneider 2009). Whereas interictal spikes occur in .5% of normally developing children without a history of epilepsy (EegOlofsson et al 1971), more recent studies have shown that up to 60% of EEG records from children with ASD have interictal spikes (Hughes and Melyn 2005) and many of the children with abnormal EEGs do not have a history of epilepsy (Hughes et al 2015).…”
Section: Prevalence Of Comorbid Autism and Epilepsymentioning
confidence: 99%
“…Some studies, especially the older reports, demonstrated higher rates of epilepsy in autistic children with a history of regression versus the autistic children without regression (79,80,103,104). These results raised the questions if there is a clinically important relation between epileptiform EEG and/or epilepsy and AR as it is shown in ESES or LKS patients.…”
Section: Controversy About Epilepsy/eeg Abnormalities In Autistic Regmentioning
confidence: 79%